Computer programme for pre-analysis and adjustment of small plane geodetic networks (horizontal controls) - 172249 Azman Mohd. Suldi (Sekudai : Universiti Teknologi Malaysia, 1986)
Tesis (Sarjana Muda Ukur (Tanah)) - Universiti Teknologi Malaysia, 1986